Rural Poverty in India: Incidence, Issues and Policies - S. Mahendra Dev; M.H. Suryanarayana; Kirit S. Parikh (Asian Development Review, 1992)
India accounts for about 14 per cent of the world’s population and about 25 per cent of that of developing countries. The number of the poor in India was about 420 million in 1985 and now represents about 38 per cent of the poor in developing countries. India has been trying to reduce poverty by adopting economic planning for growth with redistribution of income in the framework of a mixed economy…